The Correlation between Vocabulary Mastery and Their Ability in Writing Descriptive Text - Manggar Rizka Novitri; Theresia Cicik Sophia Budiman; Faiza Hawa (Universitas Majalengka, 2021)
This research is aimed to find out correlation between two variables, the vocabulary mastery as the objective variable (X) and the writing ability in descriptive text as the subjective variable (Y). The research method used is quantitative method. The population used is 7 grade of SMPN 2 Pringapus with a total of 194 students. For the sample, only one class is used, there is 7E grade with 38 students. To analyzed the instrument, there are two types of analysis, namely the technique of dividing students into three criteria and the analysis technique using Pearson Product Moment correlation. With the results, there is a significant correlation between vocabulary mastery and writing ability in writing descriptive text in 7 grade at SMPN 2 Pringapus, with the following results: With degree of significance 5%, the score of r table () obtained is 0.329, therefore, > (0.603 > 0.329), meanwhile, with degree of significance 1%, the score of rt gained is 0.424, therefore, > (0.603 > 0.424). The conclusion is HA is accepted.